Peran Zakat dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat - Karmilah Karmilah; Askari Zakariah; Novita Novita (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Zakat is one of the main pillars of Islam, required of Muslims who possess wealth exceeding the nisab threshold. Beyond its religious obligation, zakat also serves as a strategic tool for poverty alleviation and socioeconomic enhancement. The primary objective of zakat is to purify the wealth and soul of the muzakki (zakat giver) and to assist the mustahik (zakat recipients) in meeting their basic needs. In Indonesia, with its large Muslim population, the potential for zakat is significant, yet its impact on poverty reduction remains limited. Optimal zakat management is essential to ensure targeted distribution. Zakat includes eight categories of recipients: fakir, miskin, amil, muallaf, riqab, gharim, fii sabilillah, and ibn sabil. Through a productive approach, zakat can provide business capital and training to mustahik, enhancing their economic self-sufficiency and reducing social inequality. This study employs a library research method and a qualitative approach to explore the role of zakat in improving community welfare. The findings indicate that effective zakat management, especially in the form of productive zakat, can strengthen social solidarity and promote economic empowerment. Zakat functions not only as wealth redistribution but also as a holistic empowerment tool, contributing to achieving more equitable and comprehensive societal welfare.